2009
DOI: 10.1042/bc20080158
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases: salesmen and customers in the post‐translational modification market

Abstract: HDACs (histone deacetylases) are enzymes that remove the acetyl moiety from N-ε-acetylated lysine residues in histones and non-histone proteins. In recent years, it has turned out that HDACs themselves are also subject to post-translational modification. Such structural alterations can determine the stability, localization, activity and protein-protein interactions of HDACs. This subsequently affects the modification of their substrates and the coordination of cellular signalling networks. Intriguingly, physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 94 publications
(122 reference statements)
1
77
0
1
Order By: Relevance
“…One possibility is that HDAC2 is distinct from other HDAC members by post-translational modifications. It has been shown that HDAC2 protein is regulated by lysine ubiquitination, serine phosphorylation, tyrosine nitration, and cysteine nitrosylation (Sun et al 2002;Kramer et al 2003;Nott et al 2008;Adenuga et al 2009;Brandl et al 2009;Osoata et al 2009). Other ubiquitin conjugation and ligation enzymes have also been implicated in HDAC2 destruction.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that HDAC2 is distinct from other HDAC members by post-translational modifications. It has been shown that HDAC2 protein is regulated by lysine ubiquitination, serine phosphorylation, tyrosine nitration, and cysteine nitrosylation (Sun et al 2002;Kramer et al 2003;Nott et al 2008;Adenuga et al 2009;Brandl et al 2009;Osoata et al 2009). Other ubiquitin conjugation and ligation enzymes have also been implicated in HDAC2 destruction.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs play a crucial role in removing the acetyl groups from histones, thus providing a regulatory role toward the epigenetic control of gene expression (17). Presence of HDACs within the gene regulatory regions leads to formation of closed chromatin complexes (heterochromatin) resulting in gene silencing.…”
Section: Histone Deacetylasesmentioning
confidence: 99%
“…Deacetylases are frequently dysregulated in numerous tumors (7,8), Histone deacetylase 2 (HDAC2), an important member of type I histone deacetylases, plays a crucial role in tumor onset and development (8,9). Increasing evidence has revealed that HDAC2 is often overexpressed in various types of tumors (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%